The Effect of Digital Marketing Strategy and Product Innovation on the Success of Culinary MSMEs in Pangkalpinang City with Customer Satisfaction as an Intervening Variable - Fery Frandica; Suhardi Suhardi; Mat Amin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of digital marketing strategies and product innovation on the success of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Pangkalpinang City, with customer satisfaction as an intervening variable. The background of this study is based on the rapid development of the digital economy, which has driven changes in business strategies, particularly among MSMEs, as well as the increasing competition through digital-based platforms. Although the number of MSMEs continues to grow, several issues remain, including suboptimal digital marketing utilization, inconsistent product innovation, and varying levels of customer satisfaction. This study employs an explanatory quantitative approach, with data collected through questionnaires distributed to 100 culinary MSME actors selected using purposive sampling. Data analysis was conducted using multiple linear regression and path analysis to examine both direct and indirect relationships among variables. The results show that digital marketing strategies and product innovation have a positive and significant effect on both customer satisfaction and MSME success. Product innovation has a more dominant influence on customer satisfaction compared to digital marketing. In addition, customer satisfaction is proven to be the most dominant variable influencing MSME success. The mediation analysis indicates that customer satisfaction is able to mediate the effect of digital marketing strategies and product innovation on MSME success, both partially and simultaneously. Overall, this study confirms that the success of culinary MSMEs is not solely determined by digital marketing strategies and product innovation directly, but is highly influenced by the ability of business actors to create customer satisfaction. Therefore, MSME actors need to integrate digital marketing strategies with sustainable product innovation in order to enhance competitiveness and business sustainability in the digital era.